2007
DOI: 10.4049/jimmunol.179.6.3804
|View full text |Cite
|
Sign up to set email alerts
|

The B7 Homolog Butyrophilin BTN2A1 Is a Novel Ligand for DC-SIGN

Abstract: The MHC-encoded butyrophilin, BTN2A1, is a cell surface glycoprotein related to the extended family of B7 costimulatory molecules. BTN2A1 mRNA was expressed in most human tissues, but protein expression was significantly lower in leukocytes. An Ig-fusion protein of BTN2A1 bound to immature monocyte-derived dendritic cells. Binding diminished upon MoDC maturation and no binding was detected to Langerhans cells. Induction of the counterreceptor was IL-4 dependent and occurred early during dendritic cell differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
49
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 26 publications
(39 reference statements)
5
49
0
Order By: Relevance
“…1A), with very low levels of the transcript evident in other tissues as observed for Btn1a1. These results are similar to our previous studies on the orthologous human BTN2A1 gene where the transcript was detected in all tissues (30).…”
Section: Expression Of Btn1a1 and Btn2a2supporting
confidence: 82%
See 2 more Smart Citations
“…1A), with very low levels of the transcript evident in other tissues as observed for Btn1a1. These results are similar to our previous studies on the orthologous human BTN2A1 gene where the transcript was detected in all tissues (30).…”
Section: Expression Of Btn1a1 and Btn2a2supporting
confidence: 82%
“…Multiple bands were observed in DCs, indicating possible modification or differential splicing. Our findings reflect those for human BTN2A1 (30) and BTN3A1 (29), for which expression of BTN protein was detected on lymphoid and myeloid cells from peripheral blood.…”
Section: Expression Of Btn1a1 and Btn2a2supporting
confidence: 71%
See 1 more Smart Citation
“…These experiments also revealed that a particular glycosylated form of BTN2A1 binds a lectin molecule, DC-SIGN, found on DCs, confirming the involvement of the BTN family as co-regulators of the immune system [10]. Furthermore, the binding of human BTN2A1 to DC-SIGN was also dependent on heavy glycosylation of the receptor when expressed by tumor cells.…”
Section: Introductionsupporting
confidence: 49%
“…BTN2A1 is highly expressed by endothelial cells and can also be found in several tissues. DC-SIGN has been reported to be a binding partner for BTN2A1 (7), which allows the interaction with monocyte-derived DCs. BTN3 gene, which is only present in humans and not in mouse, is widely expressed in immune cells, such as T cells, B cells, NK cells, monocytes, and DCs (8).…”
mentioning
confidence: 99%